Developing Contextual Android-Based Thermodynamics Learning Media Integrating Local Coffee Drying Practices: An MDLC Approach - Singgih Bektiarso; Ernasari Ernasari; Lailatul Nuraini; Ike Lusi Meilina; Subiki Subiki; Maryani Maryani; Diana Erista Ferli; Hita Mara Cecilia; Ummi Qonitatin (Journal of Education and Teaching (JET), 2026)
This study aims to develop Android-based physics learning media on Thermodynamics material by raising the local context in the form of coffee drying process in Bondowoso Regency. The model used in the development of this media is Multimedia Development Life Cycle (MDLC) which consists of six stages, namely concept, design, material collecting, assembly, testing, and distribution. The media was designed using Android Studio, Articulate Storyline, Scratch, and Canva software, with the integration of visual, audio, animation, and interactive video elements to create interesting and contextualized learning. The design process is based on the results of field observations to obtain real data related to the stages of coffee processing, especially the drying process. The results of validation by expert validation and material validation showed an average media feasibility of 83.26%, which is included in the “very suitable” category. Thus, the learning media developed is declared suitable to be used as an alternative support for physics learning based on local wisdom, and has the potential to improve concept understanding in a more meaningful way.